Vascularized Fibula Strut Graft Used in Neurofibromatosis Type 1–Related Kyphosis: A Case of Almost Complete Reversal of Deformity-Induced Tetraparesis - Melloh, Markus; Hodgson, Bruce; Carstens, Alan; Cornwall, Jon (Evidence-Based Spine-Care Journal, 2013)
Study Design Case report.Objective The aim of this study is to describe a case of vascularized fibula strut graft implanted in the cervicothoracic spine of a patient with neurofibromatosis type 1–related progressive kyphosis.Methods A detailed history examination of the surgical procedures and the results of the follow-up after fibula strut graft implantation were performed. In addition, a review of the literature was conducted to access the incidence of similar cases with an almost complete reversal of a deformity-induced tetraparesis.Results A 37-year-old man with severe type 1 neurofibromatosis causing a collapsing kyphosis of the cervicothoracic spine presented in 2006 with progressive low cervical tetraparesis. Intervention included posterior stabilization (C5 to T5) which was extended to C3–T9 in 2008; however, the kyphosis continued to worsen. In 2009, a vascularized fibula strut graft was implanted between the inferior and superior endplates of C3 and T9. Over the following months, the patient gradually recovered motor strength and improved functional use of all limbs. In March 2011, lower limb (bilateral) and right arm strength was grade 5, with left arm strength being grade 4+.Conclusions This case report demonstrates the existence of a potential local option for the difficult problems of pseudoarthrosis, progressive spinal deformity, and cord compromise in patients with neurofibromatosis type 1–related kyphosis resulting in an almost complete reversal of deformity-induced tetraparesis.
Keywords: neurofibromatosis; cervical spine; kyphosis; tetraparesis